2020
DOI: 10.35542/osf.io/2nmxp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reading and Connecting: Using Social Annotation in Online Classes

Abstract: The COVID-19 pandemic has forced many instructors to rapidly shift to online/distance teaching. With a narrow preparation window, many instructors are at a loss of strategies that are both effective in responding to the crisis and compatible with their professional practices. This article presents a systematic literature review of the use of web annotation to support reading and discussion activities in formal education. As a genre of information systems, web annotation allows users to socially engage with web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 3 publications
0
28
0
3
Order By: Relevance
“…Using information technologies and new media becomes mandatory. Zhu et al, (2020) reported the uses of video conferencing as a method to connect learners from distance during the COVID-19.…”
Section: -Research Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using information technologies and new media becomes mandatory. Zhu et al, (2020) reported the uses of video conferencing as a method to connect learners from distance during the COVID-19.…”
Section: -Research Conclusion and Discussionmentioning
confidence: 99%
“…Thus, adopting distance learning became not an optional issue. Although distance learning makes students and staff members feel alienated and disconnected which affected student's achievement, commitment, besides attrition as stated by (Kennedy & Ferdig , 2018), video conferencing provides one way to connect learners from distance during the COVID-19 crisis (Zhu et al, 2020).…”
Section: Covid-19 Impacts On the He Sectormentioning
confidence: 99%
“…Accordingly, more attention should be paid to benefit from information technology capabilities, enhance and upgrade their websites, and keep a regular modification for their websites to be informative, clear, and recent as well. An adoption rise during the COVID-19 in the technology-based tool -solutions that enabled connections between learners was stated by (Zhu et al, 2020). The technological support that may offer an alternative such as distance learning as a mandatory option even with its social side associated issue (Kennedy & Ferdig, 2018 ).…”
Section: Research Discussion and Implicationmentioning
confidence: 99%
“…Consequently, an enlargement in the usage of technological applications and tools that support learner contacts/ connections i.e. video conferencing has been observed by (Zhu et al, 2020) Additionally, offering some services in a digital form is one of the COVID-19 identified influences, between the digital applicable services digital library services in a university (Mehta & Wang, 2020). In the same context, Kuwait University investigated by (Hendal, 2020) in regards to digital resource usage.…”
Section: Literature Review -Backgroundmentioning
confidence: 99%
“…Because of that, in K-12 students, social annotation would assist in improving language capabilities (Zhu et al, 2020) or in undergraduate classes, annotation discussion can improve reading comprehension skills.…”
mentioning
confidence: 99%